Pengungakapan CSR: Faktor Keuangan dan Non Keuangan - Kodriyah, Kodriyah; Suprihatin, Neneng Sri (Akuisisi : Jurnal Akuntansi, 2022)
This study aims to empirically examine financial and non-financial factor than can affect to Corporate Social Responsibility Disclosure The population in this study is basic and Chemical Sub Sector Manufacturing Companies listed on the Indonesian Stock Exchange for the 2016-2020 period with a sample obtained based on predetermined criteria as many as 24 companies with 105 observation data. The method used is causality design with multiple regression analysis and processed with the help of SPSS. The test results prove that company size and ownership structure have a significant influence on the Corporate Social Responsibility Disclosure, while company growth and company age do not have a significant influence on the Corporate Social Responsibility Disclosure